Good and Bad Reasoning about COVID-19 - Cummings, Louise (Informal Logic, 2020)
The Covid-19 pandemic presents argumentation theorists with an opportunity to reflect on the ways in which people, agencies and governments respond to the emergence of a new virus. Reponses have revealed a range of judgements and decisions, not all of which are rationally warranted. This article will examine errors in reasoning, several of which have reduced the public’s compliance with important health measures. This article will also analyse rationally warranted reasoning about Covid-19 employed by public health agencies. In examining instances of good and bad reasoning during the Covid-19 pandemic, we can begin to construct a taxonomy of arguments that facilitated and hindered individual and collective responses during this public health emergency.